2016
DOI: 10.15314/tjse.83415
|View full text |Cite
|
Sign up to set email alerts
|

Investigation the effects of 6 weeks pilates exercises on biomotorical variables and self-esteem scores of young women

Abstract: Purpose of this study was the investigate the effects of six weeks mat based pilates exercise on biomotirical variables and self esteem of young women. Totally 22 women (mean age; 20.1±2.2 year) participated in to the study voluntary. Participants divided into the two groups (pilates:10, control: 12) randomly. Pilates group did pilates exercise for six weeks. Control group did nothing. Pretests and post tests measurements of body height, body weight, flexibility, balance, abdominal strength and self esteem per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…The Pilates exercise group followed an original six-week Pilates mat exercise protocol created by the researchers of this study (Table I). According to previous reports, 6 to 8 weeks of Pilates training has positive effects on physical and psychological health (Bavli & Koybasi, 2016;Pourvaghar, Bahram, Sharif, & Sayyah, 2014;Rogers & Gibson, 2009). We preferred the 6-week protocol to demonstrate efficacy as soon as possible in this study.…”
Section: Pilates Mat Exercise Protocolmentioning
confidence: 93%
See 1 more Smart Citation
“…The Pilates exercise group followed an original six-week Pilates mat exercise protocol created by the researchers of this study (Table I). According to previous reports, 6 to 8 weeks of Pilates training has positive effects on physical and psychological health (Bavli & Koybasi, 2016;Pourvaghar, Bahram, Sharif, & Sayyah, 2014;Rogers & Gibson, 2009). We preferred the 6-week protocol to demonstrate efficacy as soon as possible in this study.…”
Section: Pilates Mat Exercise Protocolmentioning
confidence: 93%
“…The method is recommended by health professionals, both as rehabilitative for the people who have diseases, and preventive for undiagnosed or healthy individuals (Herrera-Gutiérrez, Olmos-Soria, & Brocal-Pérez, 2015). However, only a few clinical trials have investigated the effectiveness of Pilates training in healthy young females (Bavli & Koybasi, 2016;Caldwell et al, 2009;Kucuk & Livanelioglu, 2015;Parikh & Arora, 2016;Tolnai, Szabo, Koteles, & Szabo, 2016). Previous studies could not demonstrate the influences of Pilates-based training on psychological variables (Cruz-Ferreira et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…PEG participated in a supervised Pilates-based training program twice per week for six weeks (totally 12 sessions). Previous research demonstrated that 6 to 8 weeks of Pilates training improves physical and psychological health [25,26]. Besides, six-week Pilates exercise protocol, which consists of two sessions per week, was revealed to contribute to physical and psychological well-being in healthy individuals [13].…”
Section: Methodsmentioning
confidence: 99%
“…5,9 In addition, in most of the controlled studies, no intervention was made on the control group. 10,[14][15][16][17] Unlike the literature, our study examined the effect of clinical Pilates exercises on physical fitness, psychosocial status and exercise beliefs in healthy individuals and compared supervised and home-based clinical Pilates exercise so it differs from other studies examining the effect of clinical Pilates exercises on physical fitness, psychosocial status and exercise beliefs. Thus, our study will contribute to the literature by examining the rarely evaluated psychosocial parameters and exercise beliefs as well as physical fitness.…”
Section: Sağlıklı Kadınlarda Klinik Pilates Egzersizlerinin Fiziksel ...mentioning
confidence: 99%